The ant-nose coinage of ancient China - Walker, Thomas (KOINON: The International Journal of Classical Numismatic Studies, 2020)
The ant-nose coinage of ancient China has stumped Chinese numismatists since their discovery nearly 1000 years ago. Though aided by finds being recorded since the late 18th Century, much remains unknown about the origins of these coins and their inscriptions. This paper explores historical and archaeological evidence to determine who created them, when they were created, what inspired their creation, and how they were used in the ancient Chinese economy. In addition, theories regarding the meanings of each of the nine known inscriptions are discussed and evaluated using etymological evidence.